THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE WITH RELIGIOUS COPING AND GENERAL HEALTH OF STUDENTS - Nesami, Masoumeh Bagheri (Mater Sociomed, 2015)
AIM: This research organized to determine the relationship between Emotional Intelligence (EI) with Religious Coping and Mental Health of students at Mazandaran University of Medical Sciences. METHOD: This descriptive and analytical study was conducted in 2014 on 335 students at Mazandaran University of Medical Sciences. Students were selected by stratified random sampling method. The instruments to gather data were Bradberry and Greaves Standard Emotional Intelligence Questionnaire, the 12-item General Health Questionnaire, and the Pargament’s Religious Coping. Data was analyzed by SPSS 21 via descriptive and inferential statistics (Pearson and Spearman’s correlation). RESULTS: Among 335 students under investigation, 144 students were male (43%) and 191 ones were female (57%). Their ages were ranging from 17 to 34 years old (21.02±2.014). Average EI scores, positive religious coping, negative religious coping, and mental health were 91.27, 14.91, 4.86, 5.34, respectively. Moreover, there was a direct and significant relationship between EI and positive religious coping (r=0.282, P<0.001). CONCLUSIONS: According to the results of this study, there is a direct correlation between positive religious coping and emotional intelligence. So Strengthening religious coping can promote emotional intelligence that is one component of mental health.